Memberdayakan Kelompok Tani Melalui Optimalisasi Kebun Rumah untuk Peningkatan Ekonomi Masyarakat - Hengki Mangiring Parulian Simarmata; Henry Dunan Pardede; Erwin Sirait; Doris Yolanda Saragih; Demak Claudia Yosephine Simanjuntak; Jusra Tampubolon (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This Community Service Program (PKM) was implemented in Siantar Martoba, Pematangsiantar City, with the aim of enhancing the local economy through empowering farmer groups in optimizing backyard land. The program is a collaboration between Universitas Murni Teguh PSDKU Pematangsiantar, Politeknik Bisnis Indonesia, and the Food Security and Agriculture Office of Pematangsiantar City, attended by 15 farmers on July 4, 2025. The resource person, Henry Dunan Pardede, S.P., M.M., provided training on cultivating high-value crops such as California Papaya and Caplak Chili. The activities consisted of preparation, training, field assistance, and distribution of seedlings. The results showed an improvement in skills, entrepreneurial motivation, and more productive use of backyard land. This program also contributed to the achievement of SDGs point 1 (No Poverty), point 2 (Zero Hunger), and point 8 (Decent Work and Economic Growth) by strengthening the local economy based on agricultural potential. With a community-based approach, this program successfully increased food security, household income, and the sustainability of agricultural practices, while demonstrating the effectiveness of empowerment that can be extended to other areas facing similar challenges.